Alcohol and other drug continuing care for young people: identifying helpful program mechanisms - Max Hopwood; Joanne Bryant; Joanne Neale; Gabriel Caluzzi; Jennifer Skattebol; Sarah MacLean (International Journal of Adolescence and Youth)
‘Continuing care’ refers to the provision of co-ordinated care and support overtime. Currently, little is known about continuing care programs for young people who complete alcohol and other drug treatment. This paper analyses data from an interview-based study that aimed to identify the generative mechanisms underpinning an innovative continuing care program for young people. Researchers recruited 11 current and former program clients aged 17 to 25 years and nine program staff. Analysis identified five generative mechanisms of the program that supported participants to manage their substance use over the long term, namely person-centred counselling; relationship stability; safety and inclusion; situated mode of ordering continuing care; and organizational memory. Participants reported that the best continuing care for young people is holistic, includes regular and sustained contact, employs an innovative approach to intervention, establishes links with community services and other support structures, and provides care within a safe, person-centred, and situated framework.